Lived Experiences of Public Disability Representations: A Scoping Review - Aartjan ter Haar; Sander R. Hilberink; Alice Schippers (Disabilities)
Research has largely focussed on public perceptions of people with disabilities, particularly in the media. However, there is a lack of studies exploring how individuals with disabilities themselves experience public disability representation. This scoping review examines the lived experiences of individuals with disabilities regarding such representations. Eligible studies were peer-reviewed, published between January 1948 and July 2024, and presented qualitative findings on experienced public disability representation. A systematic search was conducted across PubMed, Scopus, ProQuest, OVID, EBSCO, and Web of Science using variations of the terms ’representation’ and ‘disability’, yielding 32 relevant studies. Data were analysed using both deductive and inductive methods. Deductive thematic analysis aligned the findings with two established media disability representation typologies: traditional and contemporary. Inductive thematic analysis identified three key themes—ignorance, incapability, and otherness—that illustrate how individuals with disabilities experience public representations. Overall, the review found that despite the absence of comparative studies, individuals with diverse disabilities report similar, predominantly negative experiences of public disability representation. Future studies should adopt an intersectional, cross-disability framework to better capture the experiences of people with disabilities, including those with intellectual disabilities.